Analisis Faktor-faktor yang Mempengaruhi Kegagalan Pasar (Market Failure) - Siti Kadariah; Rani Febriyanni; Isnaini Harahap (Universitas Batanghari Jambi, 2022)
Market failure can occur if the allocation of economic resources cannot be distributed optimally in society. In the conditions, the market will cause too much or too little of either goods or services to be produced in an economy. Market failure occurs when the market fails to allocate resources efficiently. Market failure can also be interpreted as a situation where the market does not respond to a product when there is over supply or over demand. Prices do not limit demand and cannot increase supply so that an efficient market is not created. Market failures can occur due to the following factors, namely: Asymmetric information, externalities, public goods (public), and market imperfections. This study aims to determine the factors that influence market failures that cause market imbalances. The method used is qualitative research. The results obtained from the study are market failures can occur due to factors including: Asymmetric information, externalities, public property (public), market imperfections or a decrease in average costs. To eliminate market failures, several solutions can be implemented. Use of laws & pricing mechanisms.